VAKSINASI COVID-19 YANG DIADAKAN OLEH PEMERINTAH RI DALAM UPAYA MEMERANGI PENYAKIT COVID-19 - Yana Sylvana; Muhammad Ali Hanafiah Selian (Yayasan Pendidikan Medika Indonesia, 2022)
The globe has been stunned since the end of 2019 by the emergence of the COVID-19 virus, which spreads extremely swiftly. Indonesia revealed two positive instances of COVID-19 in early March, beginning with the nation of origin, the People's Republic of China. The epidemic of COVID-19 poses a threat to the Indonesian state. The government has taken numerous measures to prevent and control the spread of this virus, including regulating activities, maintaining a safe distance, wearing masks, and washing hands, as well as producing vaccinations. The government is undertaking this effort as a sort of state defense in the fight against COVID-19. This research establishes that COVID-19 is a social disaster that affects people from all walks of life and that one option for containing the Covid-19 outbreak is for the public to participate in the vaccination campaign planned by the authorities as a form of state defense.